Mapping the Effect of Interictal Epileptic Activity Density During Wakefulness on Brain Functioning in Focal Childhood Epilepsies With Centrotemporal Spikes - Vaudano, Anna Elisabetta; Avanzini, Pietro; Cantalupo, Gaetano; Filippini, Melissa; Ruggieri, Andrea; Talami, Francesca; Caramaschi, Elisa; Bergonzini, Patrizia; Vignoli, Aglaia; Veggiotti, Pierangelo; Guerra, Azzura; Gessaroli, Giuliana; et al. (Frontiers in Neurology, 2019)
Childhood epilepsy with centrotemporal spikes (CECTS), is the most common type of “Self-Limited focal epilepsies”. In its typical presentation, CECTS is a condition reflecting non-lesional cortical hyperexcitability of rolandic regions. The benign evolution of this disorder is challenged by the frequent observation of associated neuropsychological deficits and behavioural impairment. The abundance (or frequency) of interictal centrotemporal spikes (CTS) in CECTS, is considered a risk factor for deficits in cognition. Herein we captured the hemodynamic changes triggered by the CTS density measure (i.e. the number of CTS for time bin) obtained in a cohort of CECTS, studied by means of VideoEEG/fMRI during quite wakefulness. We aim to demonstrate a direct influence of the diurnal CTS frequency on epileptogenic and cognitive networks of children with CECTS. A total number of 8950 CTS (range between 27 to 801) were recorded in 23 CECTS (21 males), with a mean number of 255 CTS/patient and a mean density of CTS/30 seconds equal to 10,866±11,46. Two independent GLM models were created for each patient based on the effect of interest: « individual CTS » in Model1, « CTS density » in Model2. Hemodynamic correlates of CTS density revealed the involvement of a widespread cortical-subcortical network encompassing the sensory-motor cortex, the Broca’s area, the premotor cortex, the thalamus, the putamen and red nucleus, while in the CTS event-related model, changes were limited to BOLD signal increases in the sensory-motor cortices. A linear relationship was observed between the CTS density hemodynamic changes and both disease duration (positive correlation) and age (negative correlation) within the language network and the bilateral insular cortices. Our results strongly support the critical role of the CTS frequency, even during wakefulness, to interfere with normal functioning of language brain networks.